Outbreak of respiratory syncytial virus (RSV) infection in immunocompromised adults on a hematology ward. Issue 10 (22nd March 2016) - Jensen, Tomas Ostergaard; Stelzer‐Braid, Sacha; Willenborg, Christiana; Cheung, Carol; Andresen, David; Rawlinson, William; Clezy, Kate
Abstract : We describe an outbreak of respiratory syncytial virus (RSV) infection on a hematology ward without allogeneic stem cell transplant patients. Twelve patients and one staff member infected with RSV were identified from the laboratory database. Five patients had lower respiratory tract infection, seven had upper respiratory tract infection, one was asymptomatic, and there were two (15.4%) deaths. Most patients had overlapping periods of potential infectiousness on the ward. Sequencing was possible on eight specimens and five of these had identical sequences. Results were consistent with transmission occurring both on the ward and by introduction of RSV from the community. J. Med. Virol. 88:1827–1831, 2016 . © 2016 Wiley Periodicals, Inc.